Thermal co-evaporated MoOx:Au thin films and its application as anode modifier in perovskite solar cells. (August 2020) - Torres-Herrera, D. Mateus; Moreno-Romero, Paola M.; Cabrera-German, Dagoberto; Cortina-Marrero, Hugo J.; Sotelo-Lerma, Mérida; Hu, Hailin
Graphical abstract: Highlights: MoOx :Au composite coatings were obtained by thermal co-evaporation method. The presence of Au in MoOx slightly reduces Mo 6+ into Mo 4+ states. MoOx :Au composite coatings are more compact and conductive than MoOx . MoOx :Au composite improves the charge transport and enhances stability of PSCs. Abstract: Molybdenum oxide (MoOx ) has been used as a suitable interfacial modifier for emergent solar cells. However, the relatively low electrical conductivity of such material requires a thickness less than 10 nm of MoOx, which may lead to an uncovered surface and reduce the effect of interfacial modification. In this work, MoO3 and Au powder were co-evaporated and MoOx :Au composite coatings with a thickness of 10–20 nm were obtained. They are highly transparent, more compact and conductive, and contain a higher percentage of MoO2 compound than MoOx films without Au. The composite films were co-evaporated on top of the hole transport layer (Spiro-MMeOTAD) in perovskite solar cells (PSCs). The insertion of a MoOx :Au composite film, with a thickness of 14.3 nm and an atomic concentration of 34% of Au, improves photovoltaic performance and stability of PSCs after 1000 h of storage in ambient conditions. It is concluded that a relatively thick MoOx :Au layer can work as an interfacial modifier to reduce the humidity and oxygen diffusion into perovskite layer and, at the same time, improve the charge transport in PSCs.